Penerapan Konsep Pendidikan Islam Dalam Pembentukan Karakter Anak Usia Dini - Moh Imam; Wawa Rijaludawa; Hoerudin (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
It is very important to apply the concept of Islamic education as early as possible because it is to foster a good personality. The purpose of this study is to find out how the application of the concept of Islamic education in the formation of early childhood character. In this study using qualitative methods. As for the technique of collecting data by observation, interviews and documentation. The results of the study are the concept of Islamic education in the formation of early childhood character through two methods, namely the method of learning and habituation. Learning and habituation can be pursued in ways that prioritize the internalization of faith values ​​in implementing character education through knowing the good, feeling the good, and acting the good.